Regulatory protein HilD stimulates Salmonella Typhimurium invasiveness by promoting smooth swimming via the methyl-accepting chemotaxis protein McpC - Kendal G. Cooper (Nature Portfolio, 2021)
Protein HilD of Salmonella Typhimurium coordinates motility and host cell invasion by upregulating flagellar genes and a secretion system. Here, Cooper et al. show that HilD also modulates swimming behaviour by upregulating a subunit of the chemotactic receptor array, and this is important for invasion of epithelial cells.